2022
DOI: 10.1186/s13617-021-00111-w
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of gap analysis for effusive crises at Piton de la Fournaise

Abstract: Effective and rapid effusive crisis response is necessary to mitigate the risks associated with lava flows that could threaten or inundate inhabited or visited areas. At Piton de la Fournaise (La Réunion, France), well-established protocols between Observatoire Volcanologique du Piton de la Fournaise – Institut de Physique du Globe de Paris (OVPF-IPGP) and civil protection, and between scientists of a multinational array of institutes, allow effective tracking of eruptive crises and hazard management embracing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
(192 reference statements)
0
15
0
Order By: Relevance
“…The creation of OVPF-IPGP was the direct result of the 1977 eruption of Piton de la Fournaise during which lava flows entered the town of Piton Sainte Rose (see Figure 1A). Today, OVPF-IPGP manages monitoring and civil protection reporting duties for volcanic and seismic hazard on La Réunion [Peltier et al 2022]. Most of the historical activity of Piton de la Fournaise has been confined to the unpopulated Enclos Fouqué caldera [Figure 1A; Harris et al 2017].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The creation of OVPF-IPGP was the direct result of the 1977 eruption of Piton de la Fournaise during which lava flows entered the town of Piton Sainte Rose (see Figure 1A). Today, OVPF-IPGP manages monitoring and civil protection reporting duties for volcanic and seismic hazard on La Réunion [Peltier et al 2022]. Most of the historical activity of Piton de la Fournaise has been confined to the unpopulated Enclos Fouqué caldera [Figure 1A; Harris et al 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a gap analysis for effusive crisis response completed by OVPF-IPGP revealed that, whereas knowledge and published experience of hazard, risk and losses during "normal" effusive crises within the caldera is excellent, as well as monitoring, mitigation, and recovery efforts in those circumstances, there is a gap for "Hors Enclos" events (i.e. those occurring beyond the caldera) [Peltier et al 2022].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations